Konservasi Mangrove : Edukasi, Aksi, dan Kolaborasi untuk Ekosistem Pesisir yang Berkelanjutan - Nugroho, Adi; Nensi, Sri Wahyu; Azharman, Zefri (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2025)
The mangrove ecosystem plays a vital role in maintaining environmental balance, making it one of the most productive ecosystems. In addition to functioning as a natural barrier against coastal abrasion, mangroves also serve as habitats for marine organisms and provide economic resources for local communities. Batam City, as an archipelagic region with approximately 13,000 hectares of mangrove potential, is facing a significant reduction in mangrove forest areas due to development and land-use conversion. In response to this condition, a community service activity was carried out in the form of mangrove tree planting as part of efforts to conserve the mangrove ecosystem. The activity took place in Kampung Terih, Batam, involving students and lecturers, and was supported by the local community. The implementation method consisted of three stages: pre-activity (location survey, stakeholder coordination, and logistical preparation), core activity (environmental education and seedling planting), and post-activity (monitoring and scientific publication). The activity resulted in the planting of approximately 200 mangrove seedlings of the Rhizophora stylosa and Bruguiera gymnorrhiza species. In addition to contributing to environmental rehabilitation, this activity had a positive impact in raising participants’ environmental awareness and providing experiential learning for students. Evaluation indicated challenges in reaching the target number of seedlings and limited information on alternative planting locations. This activity is expected to serve as a sustainable initiative for mangrove conservation in Batam’s coastal areas and to strengthen the role of educational institutions in environmental preservation through community collaboration.